PENERAPAN METODE BERMAIN BOWLING ARITMATIKA DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK USIA DINI - Sri Nurhayati (Tarbiyat al-Aulad: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Early childhood education is very important considering the potential for intelligence and the basics of a person's behavior that is formed at the age of 0-6 years. This period is so important that an early age is often referred to as the golden age. One aspect of early childhood development is cognitive development, in which there is a child's ability to recognize numbers in mathematics. Learning mathematics for early childhood is one part of education. Andriyani (2016: 3) says that in everyday life, there is one area of ​​knowledge that humans use, namely mathematics which includes addition, subtraction, division, multiplication and solving and much more. The research used is Classroom Action Research (CAR). According to Arikunto (2013: 145). Classroom action research (CAR) in general can be interpreted as an action research that is applied in teaching and learning activities in the classroom. This study uses the Jhon Elliot research model which is the development of the Khemmis & Mc Taggart model which is made more detailed at each level to make it easier for the action. Basically, the basic idea is the same, namely looking at the problem and then designing actions to solve the problem, implementing and monitoring and evaluating or reflecting and then further action will be taken if deemed necessary. Based on the results of the study, it can be concluded that the Bowling Arithmetic game can improve the cognitive development of early childhood group A. The researcher's cognitive development focuses on 3 (three) indicators that the researcher focuses on. From the data obtained by researchers in the above study, the development of numeracy through the Arithmetic Bowling game in Group A RA Al Khoeriyah before being given treatment illustrates that the average ability of pre-cycle children is in the category of children starting to develop as many as 7 children, meaning there are 87.5% and developing according to expectations there is 1 child means 12.5%. While the data obtained by researchers in the above study the development of numeracy through the Arithmetic Bowling game in Group A RA Al Khoeriyah before being given treatment illustrates that the average ability of children in cycle I is in the category of children starting to develop as many as 4 children, meaning there are 50% and developing according to hope there are 4 children means 50%.